Perception of the newly graduated nurse in nursing care during the COVID-19 pandemic: Report of experience - Silva, Vanesa Ricardo da; Frota, Francisco Ismael da Silva; Silva, Beatriz Frota da; Silva, Amanda Bernardo da (Seven Editora, 2023)
Upon being hit by the Covid-19 pandemic, and in view of the evolution of the clinical spectrum caused by the new Coronavirus, the world was faced with different challenges: development of vaccines, medications, mechanical respirators and interfaces for ventilatory therapies. At the end of December 2019, in the province of Wuhan, China, health authorities identified a set of cases of pneumonia of unknown etiology, with rapid worsening and highly transmissible. After analysis of swab samples collected from patients, the causative agent was identified as a new type of coronavirus named SARS-CoV-2 with an infectious characteristic, manifesting itself with a relevant impact on the health of the population. Also known as the new SARS-CoV2 viral syndrome, COVID manifests itself in the human body at different levels of severity. It varies between asymptomatic, mild or severe cases, and mainly affects the lower respiratory tract. DOI:https://doi.org/10.56238/globalhealthprespesc-077